Sensor and biosensor based on Prussian Blue modified gold and platinum screen printed electrodes - De Mattos, Ivanildo Luiz (2002)
Gold (Au) and platinum (Pt) screen-printed electrodes were modified with Prussian Blue (PB) for the development of amperometric sensors selective for hydrogen peroxide detection. The sensors exhibited sensitivities towards H2O2 equal to 2 A M-1 cm-2 for Au and 1 A M-1 cm-2 for Pt electrodes. The sensors were also employed as the basis for construction of glucose biosensors through further modification with crystallised glucose oxidase immobilised in a Nafion membrane. In order to improve the operational stability of the modified electrodes a buffer solution containing tetrabutylammonium toluene-4-sulfonate was used. The long-term performance of the sensors and biosensors were evaluated by continuous monitoring of hydrogen peroxide and glucose solutions (50 μM and 1 mM, respectively) in the flow-injection mode for 10 h. © 2002 Elsevier Science B.V. All rights reserved.